Change management strategy in the implementation of electronic medical record system in the era of digital transformation: Case study at Rahman Rahim Hospital - Nurmaidah, Nurmaidah; Kustiningsih, Nanik; Rahayu, Sri (Gema Wiralodra, 2024)
The problems faced by Rahman Rahim Hospital are related to implementing an electronic medical record system, so it is necessary to implement a change management strategy at the hospital. This study aims to determine change management strategies in implementing the medical record system at Rahman Rahm Hospital. The approach used in this research is descriptive qualitative. The population in this study were all employees of Rahman Rahim Sidaorjo Hospital. The sample for this research is informants or sources who are competent in providing information related to the topic of this study, namely the hospital director, head of HRD, director of medical services, and head of the IT TEAM. Data collection using interviews, observation, and documentation techniques. The data analysis used is qualitative descriptive analysis. The research results show that the duration factor and awareness of the appropriate duration have helped Rahman Rahim Hospital reduce potential resistance and discomfort during the transition, paving the way for smooth adoption. Second, the integrity factor, system integration with established clinical processes, and maintaining data accuracy are the keys for Rahman Rahim Hospital to reduce conflict and increase staff and medical practitioners' acceptance of change. Third, the commitment factor, concrete efforts, such as effective communication, active participation, and ongoing support, are used by Rahman Rahim Hospital to build strong commitment at all levels of the organization. Fourth, the effort factor and investment in human and financial resources, together with managing obstacles and challenges through strategies such as employee training, expert consultants, and improving technological infrastructure, are the keys to Rahman Rahim Hospital in optimizing efforts to face digital transformation.